Optimizing Spare Parts Inventory and Logistics for Maximum Plant Uptime in the Energy Sector - Narayanan, Shankar Bhaskaran (ExcelingTech, 2025)
Equipments play a critical role in Oil Gas (ONG) operations. Failure of their proper and efficient functioning has direct and significant bearing on plant uptime, energy output and supply chain (SC) stability. This article delves into the mechanical failure modes and predictive maintenance techniques, to enhance spare part forecasting. It establishes the usefulness of predictive analytics in deciding optimum spare parts inventory levels necessary for ensuring cost rationalization for balancing operational cost and efficiency. The article focuses on the application of sophisticated technology for achieving maximum plant uptime.